2019
DOI: 10.1007/s10120-019-00926-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of early genetic changes in well-differentiated intramucosal gastric carcinoma by target deep sequencing

Abstract: Background and aimsThe recent advancement of next-generation sequencing (NGS) has enabled the identification of cancerrelated somatic aberrations in advanced gastric cancer. However, these remain unclear in early gastric cancers, especially in intramucosal gastric cancers. Patients and methods Thirty-one well-differentiated (tub1) intramucosal gastric cancers obtained by endoscopic submucosal dissection (ESD) from 29 patients were analyzed. After precise collection of tumors and non-tumors from formalin-fixed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
1
11
1
Order By: Relevance
“…Moreover, Yoshida et al performed target sequencing on 50 genes for 31 non-invasive GCs. They reported that mutation in TP53 and Wnt-signaling pathway genes (APC and CTNNB1) were frequently found and were mutually exclusive [32]. This result is almost the same in our data, that is, 10 out of 12 cases with TP53 mutation had no mutation in APC and CTNNB1.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Moreover, Yoshida et al performed target sequencing on 50 genes for 31 non-invasive GCs. They reported that mutation in TP53 and Wnt-signaling pathway genes (APC and CTNNB1) were frequently found and were mutually exclusive [32]. This result is almost the same in our data, that is, 10 out of 12 cases with TP53 mutation had no mutation in APC and CTNNB1.…”
Section: Discussionsupporting
confidence: 88%
“…This result is almost the same in our data, that is, 10 out of 12 cases with TP53 mutation had no mutation in APC and CTNNB1. Furthermore, the frequency of the following gene mutations did not differ significantly between our data and their data (ARID1A, ARID2, APC, SMAD4, PIK3CA, RHOA, KRAS, MUC6, and APC: Fisher's exact test, data not shown) [14,32]. However, LRP1, which was detected as a significant gene mutation following TP53 in our study was not included in their target-sequencing panel.…”
Section: Discussioncontrasting
confidence: 59%
“…Clinically relevant biomarkers are genetic, epigenetic, proteinic, or cellular alterations that are intrinsic to cancer cells. These biomarkers can be used to predict patients' responses to Huang et al [50] , 2017 Pasternack et al [112] , 2018 Kakiuchi et al [42] , 2014 Yoshida et al [113] , 2019 Nagahashi et al [39] , 2016…”
Section: Biomarkers For Gi Cancermentioning
confidence: 99%
“…These different subtypes exhibit unique molecular features that could potentially be used to guide therapeutic decisions, and have been shown to have prognostic signi cance; for example, Epstein-Barr virus (EBV) infection has been associated with improved prognosis. Since the molecular classi cation of GC has potential prognostic and therapeutic implications, it may be used identify biomarkers and therapeutic targets for each subtype, particularly through strati cation according to EBV infection and microsatellite instability (MSI) [4][5][6][7][8]. Currently, the expression of programmed death-ligand 1 (PD-L1) in tumor cells is a validated predictive marker for the tumor response to anti programmed cell death-1 protein (anti-PD-1) or PD-L1 immunotherapy in different malignancies, including GC [9].…”
Section: Introductionmentioning
confidence: 99%